Managing nitrogen for sustainable crop production with reduced hydrological nitrogen losses under a winter wheat–summer maize rotation system: an eight-season field study - Wang, Li; Ma, Lei; Li, Yan; Geilfus, Christoph-Martin; Wei, Jianlin; Zheng, Fuli; Liu, Zhaohui; Tan, Deshui (Frontiers in Plant Science, 2023)
Excessive nitrogen (N) application in wheat-maize cropping system was adjusted towards more sustainable practices to reduce hydrological N losses while maintaining crop yield. In comprehensive quantification of N management effects on crop yield, N use efficiency (NUE), hydrological N losses and soil nitrate residual across eight seasons, we have added to growing evidence of strategies beneficial for sustainable crop production with lower hydrological N losses. The results show that adjusted N practices enhanced crop yield and NUE, as compared to farmer's practice, but benefits varied with N rates and types. Optimized N treatment (OPT, 180 kg N ha -1 in both maize and wheat seasons) with or without straw returning produced most crop yield. They increased maize yield by 5.5%, 7.3%, and wheat yield by 6.2%, 3.2% on average, as compared to farmer's practice with huge N application (FP, 345 and 240 kg N ha -1 in maize and wheat). Regulation of N release through amendment with controlled release urea at a rate of 144 kg N ha -1 crop -1 (CRU treatment) obtained 4.4% greater maize yield than FP, and sustained a similar wheat yield with less N input, resulting in the highest crop NUE. Additionally, CRU was most effective in mitigating hydrological N loss, with 39.5%, 45.5% less leachate N, and 31.9%, 35.9% less runoff N loss than FP in maize and wheat seasons. Synthetic N input correlated significantly and positively with runoff and leachate N losses, indicating it was one of the dominating factors driving hydrological N losses. Moreover, compared to OPT, additional straw returning (STR) or substituting 20% of the nutrients by duck manure (DMS) further reduced runoff N discharges due to the fact that organic matter incorporation increased resilience to rainfall. N over-application in FP caused considerable nitrate accumulation in the 0-90 cm soil profile,